Pengaruh Minat Belajar terhadap Prestasi Belajar Akademik dan Non Akademik Bagi Siswa pada Madrasah Aliyah (MA) Kota Samarinda - Amrullah, Amrullah (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2018)
This research is based on the phenomenon in the field which shows that there is an influence of interest in learning on academic achievement and non-academic achievement for students at the Madrasah Aliyah (MA) of Samarinda City. This study aims to describe the influence of interest in learning on academic achievement and the effect of academic achievement on non-academic achievement for students at the Madrasah Aliyah (MA) in Samarinda city. The study population was all students of the madrasah aliyah (MA) in the city of Samarinda, totaling 2262 students. The sample was set at 663 students who sat in class XI. the determination of madrasas is determined through purposive sampling. While the selection of respondents was done using a multi-stage sampling technique which was set at 87 students (respondents). Data collection uses questionnaires, while data analysis techniques use multiple correlation analysis. The results showed that the influence of partial interest in learning contributed to a correlation of 6% with academic achievement. This means that the students of Aliyah Madrasah in Samarinda have a very strong interest in learning about academic achievement. The hypothesis which states the existence of a correlation that has significance between the influence of interest in learning and academic achievement is accepted the truth, as evidenced by the value of t count = 2.327 and the distribution table t = -3.3324. Because t counts ˃t table then H0 is rejected. At a significant level Sig.0,001 and α = 0,05 were obtained. Because α = 0.05˃ Sig. = 0.001, then H0 is rejected and the effect of partial interest in learning has a correlation of 12.1% with non-academic achievements. This means that students of the Aliyah Madrasah in Samarinda have a good or very strong interest in learning about non-academic achievements. The hypothesis which states the existence of a correlation that is significant between the influence of interest in learning and non-academic achievement is accepted, as evidenced by the value of t count = 34.20 and the distribution table t = -3.3324. Because t counts ˃t table then H0 is rejected. At a significant level Sig.0,001 and α = 0,05 were obtained. Because α = 0.05˃ Sig. = 0.001, then H0 is rejected.